Seeing beyond the House: Historic Structures as Museums. Issue 1 (March 2014) - Fitzpatrick, Siobhan
This essay examines five historic structures two mills, a library, a custom house and a retirement community that have been converted to serve as museums. Each case study looks at the building location, building ownership and interpretation of the structure.